Pengukuran Kepuasan Kontraktor terhadap Kinerja Klien pada Proyek Konstruksi Pemerintah - Noviana Dwi Hastuti; Neno Ayu Luthfia; Jati Utomo Dwi Hatmoko; Frida Kistiani (Departemen Teknik Sipil, Fakultas Teknik Universitas Diponegoro, 2013)
Assessment of contractor satisfaction towards client performance of government-funded construction projects in Semarang. Research conducted to identify client performance that cause dissatisfaction. Six indicators were used i.e: understanding of project requirements, finance, decision making, management skills, support to contractor, attitude which developed into variable. The contractor satisfaction assessment obtained from Customer Satisfaction Index (CSI) and Importance Performance Analysis (IPA) method. Results of analysis client satisfaction performance level and determine the variables that are to be improved. The results can be used as feedback for clients to improve their performance in construction project.